QUESTIONS AS ONE OF THE MEANS OF DEVELOPMENT COGNITIVE ACTIVITY OF SENIOR STUDENTS (Pedagogy of Higher and Secondary Education, 2003)
The article is dedicated to the problem of forming o f the activity of pupils’ cognitive work, the development o f the skills of asking and answering the questions.